It's an arithmetic sequence:
The explicit rule:
Substitute:
B. Obtuse
C. Adjacent
D. Vertical
Which of the following functions best defines this sequence? (5 points)
A f(1) = 9, f(n + 1) = f(n) − 4; for n ≥ 1
B f(1) = 9, f(n + 1) = f(n) + 4; for n ≥ 1
C f(1) = 9, f(n + 1) = f(n) − 5; for n ≥ 1
D f(1) = 9, f(n + 1) = f(n) + 5; for n ≥ 1
Answer:
Option A is correct.
Step-by-step explanation:
We have been given the sequence:
9,5,1,-3
We can clearly see that the next digit is four less than the previous digit.
Here first term that is a=9
So, the function would be:
Therefore. option A is correct.
Option B and D are not correct because function is decreasing not increasing.
Option C is not correct because decreasing by 4 not 5.
Answer:
A f(1) = 9, f(n + 1) = f(n) − 4; for n ≥ 1
Step-by-step explanation:
i took the test and got it right
Answer:
(15x - 4) units
Step-by-step explanation:
5x-2 + 4x-4 + 6x - 8
15x - 14
multiply polynomials (2n+2)(6n+1)
The multiplication of the expression ( 2n + 2 )( 6n + 1 ) is 12n² + 14n + 2.
Given the expression in the question:
( 2n + 2 )( 6n + 1 )
To multiply the expression ( 2n + 2 )( 6n + 1 ), we use the distributive property and the FOIL method.
( 2n + 2 )( 6n + 1 )
Using the Foil method:
2n( 6n + 1 ) + 2( 6n + 1 )
Using the distributive property:
2n × 6n + 2 × 1 + 2 × 6n + 2 × 1
Multiplying, we get:
12n² + 2n + 12n + 2
Collect and add the like terms:
12n² + 14n + 2
Therefore, the simplified form is 12n² + 14n + 2.
Learn more about the FOIL method here: brainly.com/question/27980306
#SPJ6